2014
DOI: 10.1055/s-0034-1374586
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Comparison of Add-on Therapy with Liraglutide, Saxagliptin and Vildagliptin, All in Combination with Current Conventional Oral Hypoglycemic Agents Therapy in Poorly Controlled Chinese Type 2 Diabetes

Abstract: To compare the efficacy and safety of adding liraglutide, saxagliptin and vildagliptin to current therapy in Chinese type 2 diabetes subjects with poor glycemic control.A 24-week, randomized, open-label, parallel clinical trial was performed. A total 178 patients completed the trial who had been randomly assigned to add-on once daily liraglutide (1.2 mg/day injected subcutaneously), to saxagliptin (5 mg once daily) or to vildagliptin (50 mg twice daily). Glycosylated hemoglobin (HbA1c) values, fasting and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…Our study supports previous data on liraglutide improvements in glucose control and weight reduction. HbA1c improvement was directly related to basal HbA1c in concordance with previous studies [9][10][11]. As indicated in our study, greater proportion of patients treated with liraglutide reached the target level of HbA1c < 7% than the other two agents, without accompanying an increased risk of hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study supports previous data on liraglutide improvements in glucose control and weight reduction. HbA1c improvement was directly related to basal HbA1c in concordance with previous studies [9][10][11]. As indicated in our study, greater proportion of patients treated with liraglutide reached the target level of HbA1c < 7% than the other two agents, without accompanying an increased risk of hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies indicated that both GLP-1RA and DPP4i have the priority over metformin and sulfonylurea in reducing plasma glucose and body weight, and increasing insulin sensitivity. However, these studies seldom select the newly diagnosed diabetic patients as subjects, and rarely evaluate the adipokines profile [8][9][10][11]. To our knowledge, no studies have addressed the effect of liraglutide and sitagliptin treatment on plasma glycemic control, weight loss and circulating adipokines in newly diagnosed diabetic patients in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, body weight loss was greater with exenatide QWS‐AI than with placebo but similar to body weight loss with sitagliptin. Among earlier studies comparing GLP‐1RAs with DPP‐4is, all but 2 found significantly greater body weight reductions with GLP‐1RAs over 24 to 104 weeks. The similar body weight loss seen with exenatide QWS‐AI and sitagliptin in this study may be explained by body weight loss with exenatide QWS‐AI being somewhat lower than expected.…”
Section: Discussionmentioning
confidence: 94%
“…Of 8 randomized, head‐to‐head studies comparing the GLP‐1RAs exenatide, liraglutide, albiglutide or dulaglutide with the DPP‐4i sitagliptin as add‐on therapy or monotherapy, 6 studies demonstrated significantly greater HbA1c reductions over 26 to 104 weeks with GLP‐1RAs vs sitagliptin; 1 24‐week study found no significantly different reductions with liraglutide 0.9 mg/d vs sitagliptin, and 1 26‐week study found that sitagliptin was noninferior to liraglutide 1.2 mg/d . Additionally, a 24‐week study found significantly greater HbA1c reductions with liraglutide vs saxagliptin or vildagliptin . In 7 of the 9 earlier studies, proportions of patients achieving HbA1c levels <7.0% were greater with GLP‐1RAs than DPP‐4is …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation